Enrichments/Derichments of Root-Associated Bacteria Related to Plant Growth and Nutrition Caused by the Growth of an EPSPS-Transgenic Maize Line in the Field - Wen, Zhong-Ling; Yang, Min-Kai; Du, Mei-Hang; Zhong, Zhao-Zhao; Lu, Yun-Ting; Wang, Gu-Hao; Hua, Xiao-Mei; Fazal, Aliya; Mu, Chun-Hua; Yan, Shu-Feng; Zhen, Yan; Yang, Rong-Wu; et al. (Frontiers in Microbiology, 2019)
During the past decades, the effects of the transgenic crops on soil microbial communities have aroused widespread interest of scientists, which was mainly related to the health and growth of plants. In this study, the maize root-associated bacterial communities of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) transgenic glyphosate-tolerant (GT) maize line CC-2 (CC2) and its recipient variety Zhengdan958 (Z958) were compared at the tasseling and flowering stages by high-throughput sequencing of V3-V4 hypervariable regions of 16S rRNA gene (16S rDNA) amplicons via Illumina MiSeq. In addition, real-time quantitative PCR (qPCR) was also performed to analyze the nifH gene abundance between CC2 and Z958. Our results showed no significant difference in alpha/beta diversity of root-associated bacterial communities at the tasseling or flowering stage between CC2 and Z958 under field growth conditions. The relative abundances of the genera Bradyrhizobium and Bacillus including species B. cereus and B. muralis were significantly lower in the roots of CC2 than that of Z985 under field conditions. Both these species are regarded as plant growth promoting bacteria (PGPB), as they belong to both nitrogen-fixing and phosphate-solubilizing bacterial genera. The comparison of the relative abundance of nitrogen-fixing/phosphate-solubilizing bacteria at the class, order or family levels indicated that only one class Bacilli, one order Bacillales and one family Bacillaceae were found to be significantly lower in the roots of CC2 than that of Z985. These bacteria were also enriched in the roots and rhizospheric soil than in the surrounding soil at both two stages. Furthermore, the class Betaproteobacteria, the order Burkholderiales, the family Comamonadaceae and the genus Acidovorax were significantly higher in the roots of CC2 than that of Z985 at the tasseling stage, meanwhile the order Burkholderiales and the family Comamonadaceae were also enriched in the roots than in the rhizospheric soil at both stages. Additionally, the nifH gene abundance at the tasseling stage in the rhizosphere soil also showed significant difference. The relative abundance of nifH gene was higher in the root samples and lower in the surrounding soil, which implicated that the roots of maize tend to be enriched in nitrogen-fixing bacteria.